THE RELATIONSHIP BETWEEN PHYSICAL ACTIVITY AND DEPRESSION OF CHINESE STUDENTS STUDYING IN RUSSIA - Yajun Zhang; Tatyana Aleksandrovna Shilko (Физическая культура. Спорт. Туризм. Двигательная рекреация, 2020)
To understand the effect of physical activity on the depression status of Chinese students studying in Russia. The authors used the SDS depression self-assessment scale and physical exercise assessment scale to survey 350 Chinese students in some Russian universities, and collected the questionnaires on their mobile phones. The basic situation was investigated and the data was analyzed statistically. Use SPSS to assess the correlation between physical activity and depression. It was found that appropriately increasing the amount of physical activity can effectively improve depression and be beneficial to the development of mental health of Chinese students studying in Russia.